Análisis de la cultura organizacional y modelo de desarrollo organizacional en la institución educativa Jiménez. - Jimenez Piedra, Erika Marisela (My University, 2019)
The present research work carried out at the Jiménez Educational Institution aims to describe the organizational culture through the inquiry of the values of each member of the company and propose the development model of Kurt Lewin that contributes to the planned change through the phases of the same, defrosting, movement or change and freezing. The qualitative descriptive method and tools such as participant observation and interview with the 28 members of the Educational Institution were used to carry out the investigation. It was thus achieved through the Lewin model to propose values and principles with which the staff identifies to improve the organizational culture, generate the planned change, improve the services and the performance of the staff. Once these values and principles have been socialized, the interest groups assume the commitment and show a predisposition towards the proposal, focused on the Educational Institution being the most competitive in the educational sector with solid organizational values and principles. It is clear that Kurt Lewin's model is once again the best option to generate the planned change.
El presente trabajo de investigación realizado en la Institución Educativa Jiménez tiene como objetivo describir la cultura organizacional a través de la indagación de los valores de cada miembro de la empresa y proponer el modelo de desarrollo de Kurt Lewin que contribuya al cambio planeado a través de las fases del mismo, descongelamiento, movimiento o cambio y congelamiento. Para realizar la investigación se utilizó el método cualitativo descriptivo y herramientas tales como la observación participante y entrevista a los 28 miembros de la Institución Educativa. Se logró así a través del modelo de Lewin proponer valores y principios con los cuales el personal se identifica para mejorar la cultura organizacional, generar el cambio planeado, mejorar los servicios y el desempeño del personal. Una vez socializados dichos valores y principios los grupos de interés asumen el compromiso y denotan predisposición ante la propuesta, enfocados en que la Institución Educativa sea la más competitiva en el sector educativo con valores y principios organizacionales sólidos. Queda claro que el modelo de Kurt Lewin se constituye una vez más en la mejor opción para generar el cambio planeado.
Keywords: CULTURA ORGANIZACIONAL; MODELO DE DESARROLLO; VALORES; PRINCIPIOS